2000
DOI: 10.1143/jpsj.69.3860
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectra Calculation of Ordered-Vacancy Ga2Se3Compounds; Origin of Anisotropy

Abstract: Polarized Raman spectra of ordered-vacancy Ga 2 Se 3 were calculated using the sp 3 s * tightbinding and vibration models. We found a large peak around 150 cm −1 which originates from the breathing-like movement of Se atoms around the vacancy. Reflecting the localized nature of vibration and the dangling-bond direction of three-coordinated Se atoms, this peak shows large intensity and anisotropy; the intensity is large for the light polarization perpendicular to the vacancy array, in contrast to the anisotropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…In fact, Ohmura et al predicted the presence of a peak at 160 cm −1 in the spectrum of β-Ga 2 Se 3 , which was attributed to the localized breathing motion of Se 1/3 atoms. 31 Furthermore, similar to the suggestion of 3-fold coordinated Se atoms in Sedeficient Ge−Se glasses, the presence of analogous 3-fold coordinated S atoms has also been proposed in Ge-rich Ge−S glasses with ≥36 atom % Ge, in a recent structural study based on combined X-ray and neutron diffraction. 42 However, the most convincing evidence for the presence of higher coordinated Se 1/3 sites in GGS glasses comes from the 77 Se MAS NMR spectra (Figure 2).…”
Section: Experimental Methodssupporting
confidence: 54%
See 3 more Smart Citations
“…In fact, Ohmura et al predicted the presence of a peak at 160 cm −1 in the spectrum of β-Ga 2 Se 3 , which was attributed to the localized breathing motion of Se 1/3 atoms. 31 Furthermore, similar to the suggestion of 3-fold coordinated Se atoms in Sedeficient Ge−Se glasses, the presence of analogous 3-fold coordinated S atoms has also been proposed in Ge-rich Ge−S glasses with ≥36 atom % Ge, in a recent structural study based on combined X-ray and neutron diffraction. 42 However, the most convincing evidence for the presence of higher coordinated Se 1/3 sites in GGS glasses comes from the 77 Se MAS NMR spectra (Figure 2).…”
Section: Experimental Methodssupporting
confidence: 54%
“…Rather, the frequency of the Raman band at ∼160 cm –1 is comparable to the ∼152 cm –1 band in the Raman spectrum of crystalline Ga 2 Se 3 (Figure ) that was associated with the motion of Se 1/2 and Se 1/3 atoms around Ga vacancies. In fact, Ohmura et al predicted the presence of a peak at 160 cm –1 in the spectrum of β-Ga 2 Se 3 , which was attributed to the localized breathing motion of Se 1/3 atoms . Furthermore, similar to the suggestion of 3-fold coordinated Se atoms in Se-deficient Ge–Se glasses, the presence of analogous 3-fold coordinated S atoms has also been proposed in Ge-rich Ge–S glasses with ≥36 atom % Ge, in a recent structural study based on combined X-ray and neutron diffraction …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In our previous works, it was shown that the dangling bonds of two-coordinated Se in Ga 2 Se 3 produce one-dimensional band along the [ 1 110] direction at the valence band top and the optical transitions from this band to the conduction bands become the origin of such anisotropies [6,7]. In this view, one can expect that the p-doping into Ga 2 Se 3 might induce the one-dimensional conductivite properties.…”
mentioning
confidence: 97%